Chissano contra Machel e o Colono: representações sociais do estado em Moçambique - Gabriel Mithá Ribeiro (Cadernos de Estudos Africanos)
This text presents the preliminary results of an ongoing research on political dimension of social thinking in Mozambique. Based on a case study in the city of Tete, the text analyses (and problematises) the validity and the pertinence of the theoretical assumptions adopted in the study of social thinking about «politics». Indeed, several theoretical and methodological questions are raised in order to stimulate the academic debate and contribute to a greater understanding of the problems associated with the study of «social dimension» of politics, as well as the attitudes and social practices associated with them.